Teaching an entrepreneurship lab : lessons learned / Eric J. Romero and Kim T. Hinrichs - J. Romero, Eric; T. Hinrichs, Kim (Faculty of Business and Management ; UiTM Press, 2000)
The lessons learned from teaching an entrepreneurship lab are presented and discussed. Students participated in a course where they started a small business selling merchandise on an online auction service. The basic structure of the course, problems with the initial design, and future improvements in the course will be described. Student feedback on their perceptions of the various aspects of the course is also presented. Finally, some helpful suggestions are offered for instructors interested in teaching a similar course. The course described in this paper might be an attractive option for universities interested in offering new courses in entrepreneurship.